ART NOUVEAU STYLE BUILDINGS AS A CHANCE FOR THE DEVELOPMENT OF ARCHITECTURE IN NOVI SAD - Mijuk, Nenad (The Business of Tourism, 2022)
Abstract: By the end of the 20th century, a new specific form of tourism was presented to the world by the name of architourism. Architecture, in a general sense, is science and the art of projecting and shaping buildings or, i.e., interior and exterior architectural space. Novi Sad, the second largest city in Serbia, located on Pannonian Plain, is famous for its incredibly rich historic and cultural heritage. There are various styles of architecture dominating the city itself, among which is the ever-present Art Nouveau in the Hungarian style. Novi Sad has fewer monuments and buildings erected in this style, as opposed to Subotica, but they are very high-quality and distinctive. Some influential architects had worked in that period in Novi Sad, and on top of that list was Lipot Baumhorn, responsible for the Synagogue, Menratova palace, the palace of “Vojvođanska banka“, followed by Karolj Kovač, Đerđ Kopecki, Imre Frensek, Geza Markuš, Frđeš Špigel, Bela Peko, and others. This paper aims to emphasize the cultural-historic influence of buildings in the Art Nouveau style as a significant form of tourism.